A Simple Technique for the Positioning of a Patient with an above Knee Amputation for an Ipsilateral Extracapsular Hip Fracture Fixation. (12th December 2013) - Davarinos, N.; Ellanti, P.; McCoy, G.
Abstract : The positioning of the patient on the fracture table is critical to the successful reduction and operative fixation of hip fractures which are fixed using the dynamic hip screw system (DHS). There is a standard setup which is commonly used with relative ease. Yet the positioning of patients with amputations either above or below knee of the affected side can pose a significant challenge. We describe a novel positioning technique used on a 51-year old patient with a right above knee amputation who sustained an intertrochanteric extracapsular hip fracture.